Correlation between type 2 diabetic nephropathy and retinopathy - ZOU Gu-ming; ZHANG Nian-rong; GAO Hong-mei; LU Jian-hua; ZHUO Li; LI Wen-ge (Linchuang shenzangbing zazhi)
Objective Currently mechanisms of diabetic nephropathy(DN) and diabetic retinopathy(DR),which are two most common complications of diabetic microvascular disease,remain unclear.In this study,correlation between DN and DR was analyzed.Methods 95 cases with type 2 diabetes in the department of nephrology of China-Japan Friendship Hospital from January,2004 to December,2014,which were diagnosed as DN by renal biopsy,were selected and divided into five DN(Ⅰ,Ⅱa,Ⅱ b,Ⅲ and Ⅳ) groups according to the renal pathologic changes.Retinal changes in different groups(DR0,DR1 and DR2) were compared and correlation of renal pathology with retinal changes were analyzed.Correlations between retinal changes and some clinical indices were also analyzed.Results There was a significant correlation between DN groups(Ⅰ,Ⅱ a,Ⅱ b and Ⅲ) and different retinal changes(DR0 and DR1).The rate of patients without DR was 23.2%in all the 95 patients,80.00%in group DN I,33.33%in group DN Ⅱ a,12.50%in group DN Ⅱb,and 14.81%in group DN Ⅲ.Among clinical indices,only 24-hour urinary protein predicted development of DR.Conclusions Though DR is usually considered as a diagnosed marker for most DN patients,a small number of DN patients without DR should be paid attention to the diagnosis of DN.